ЕКРАНУВАННЯ МАГНІТНОГО ПОЛЯ ПІДЗЕМНОЇ КАБЕЛЬНОЇ ЛІНІЇ ЗА ДОПОМОГОЮ Н-ПОДІБНОГО ЕКРАНА - Кучерява, І.М. (Інститут електродинаміки НАН України, Київ, 2020)
In the article the magnetic field distributions, generated by underground extra-high voltage (330 kV) three-phase power cable line in the environment, in particular near the cables in the trench and on the ground, are analyzed for using of H-shaped shield made of different materials including aluminum, low carbon steel and non-oriented grain steel. As shown, the best shielding effectiveness is realized by aluminium shield. The H-shaped shield made of high-conducting non-magnetic materials is proposed to use in order to mitigate the magnetic field level on the ground down to regulated nonhazardous values. References 14, figures 7.